The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/jocs.16009
|View full text |Cite
|
Sign up to set email alerts
|

Early onset of deep sternal wound infection after cardiac surgery is associated with decreased survival: A propensity weighted analysis

Abstract: Objectives: To compare outcomes after the development of early (≤30 days) versus delayed (>30 days) deep sternal wound infection (DSWI) after cardiac surgery. Methods: Between 2005 and 2016, 64 patients were treated surgically for DSWI following cardiac surgery. Thirty-three developed early DSWI, while 31 developed late DSWI. The mean follow-up was 34.1 ± 32.3 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Inadvertent paramedian sternotomy inhibits optimal approximation and alignment of the sternal edges, optimal bone healing, and chest wound stability. 19) As demonstrated in our study, Flexigrip may be useful for optimal approximation and alignment of the sternal edges to produce bone healing and chest stability. Especially, improved bone union was achieved at the manubrium when the method of closure was the same wiring in this region in both cohorts of Flexigrip and wiring.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Inadvertent paramedian sternotomy inhibits optimal approximation and alignment of the sternal edges, optimal bone healing, and chest wound stability. 19) As demonstrated in our study, Flexigrip may be useful for optimal approximation and alignment of the sternal edges to produce bone healing and chest stability. Especially, improved bone union was achieved at the manubrium when the method of closure was the same wiring in this region in both cohorts of Flexigrip and wiring.…”
Section: Discussionmentioning
confidence: 60%
“…Our results may support the findings of the previous reports [6][7][8] of more excellent clinical outcomes of Flexigrip than wiring. Recently, Elsayed et al 19) demonstrated that the patients diagnosed with deep sternal wound infection early (≤30 days) after cardiac surgery have increased mortality than those with late onset (>30 days) infection, speculating a greater aggressiveness of the early onset infection. Therefore, early osteosynthesis (solid bony union) with Flexigrip, as demonstrated in our study, is strongly desired to prevent early onset of sternal infection.…”
Section: Discussionmentioning
confidence: 99%